2004
DOI: 10.1177/019027250406700205
|View full text |Cite
|
Sign up to set email alerts
|

Legitimacy and Justice Perceptions

Abstract: Consistent with the theoretical argument of Hegtvedt and Johnson, we empirically examine the relationship between collectivity-generated legitimacy of reward procedures and individual-level justice perceptions about reward distributions. Using data from a natural setting, we find that collectivity sources of validity (authorization and endorsement) exert positive effects on individual-level justice perceptions as predicted by Hegtvedt and Johnson, but that this influence is entirely indirect through the indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 21 publications
(22 reference statements)
1
10
0
2
Order By: Relevance
“…This finding has been reported in studies that examined both criminal justice contexts (Mastrofski, Snipes, & Supina, 1996;Paternoster, Brame, Bachman, & Sherman, 1997;Piquero, Gomez-Smith, & Langton, 2004;Sherman, 2002;Sunshine & Tyler, 2003b;Tyler, 2004;Tyler & Wakslak, 2004) and noncriminal justice contexts (Kitzmann & Emery, 1993;Lind, Kulik, Ambrose, & Deverapark, 1993;Mueller & Landsman, 2004;Pruitt, Peirce, McGillicuddy, Welton, & Castrianno, 1993). Restorative-based justice and justice conferencing programs have also been developed, which define the role of justice professionals more as intermediaries between the state and citizens than as authoritarian decision-makers in the criminal justice process (Olson & Dzur, 2004).…”
Section: Introductionsupporting
confidence: 54%
“…This finding has been reported in studies that examined both criminal justice contexts (Mastrofski, Snipes, & Supina, 1996;Paternoster, Brame, Bachman, & Sherman, 1997;Piquero, Gomez-Smith, & Langton, 2004;Sherman, 2002;Sunshine & Tyler, 2003b;Tyler, 2004;Tyler & Wakslak, 2004) and noncriminal justice contexts (Kitzmann & Emery, 1993;Lind, Kulik, Ambrose, & Deverapark, 1993;Mueller & Landsman, 2004;Pruitt, Peirce, McGillicuddy, Welton, & Castrianno, 1993). Restorative-based justice and justice conferencing programs have also been developed, which define the role of justice professionals more as intermediaries between the state and citizens than as authoritarian decision-makers in the criminal justice process (Olson & Dzur, 2004).…”
Section: Introductionsupporting
confidence: 54%
“…In this case, referred to by them as the utopian perspective, we would find consensus among individuals regarding a just distribution. On the other hand, there is the existential perspective, which states that, instead of appealing to general normative principles, what people consider as just is mostly based on the elements that characterise their day‐to‐day reality (Shepelak and Alwin, 1986; Kluegel et al, 1995; Mueller and Landsman, 2004). Berger takes this line of reasoning, pointing out that an individual ‘believes he should possess what he believes others like him do possess' (Berger et al, 1972: 139), and therefore justice depends on a comparative process against some referential standard of the context.…”
Section: Explaining Individual Differences In the Justification Of Inmentioning
confidence: 99%
“…A one-time distribution of unfair outcomes by a legitimate authority for unknown reasons is likely to result in an external attribution (Kelley, 1973) and to fuel the idea that the decision is within the authority's purview, thereby reducing the perceived severity of injustice. Mueller and Landsman (2004) showed that authorisation and endorsement enhanced distributive justice perceptions, although procedural justice mediated their direct effects.…”
Section: Observers' Perceptions Of Distributive Injustice Suffered Bymentioning
confidence: 96%